Analisis Brand Engagement dan Pengalaman Pelanggan sebagai Mediasi Pengaruh Gamification terhadap Loyalitas Pelanggan Shopee - Dimas Fahrur Rozi (Fakultas Ekonomi dan Bisnis, 2025)
The practice of utilizing e-commerece for shopping has become a prevalent habit within Indonesian society. The Indonesian populance has greeted the advent of e commerce with enthusiasm, as evidenced by predominance of Shopee, a prominent e-commerce platform, in the domestic market. As a technology-based servvice provider, shopee endeavors to enhance its services through the implementation of gamification, facilitated by the Shopee Games feature. This research endeavors to elucidate effective strategies for developing features in an application to enhance brand engagement, customer experience, and loyalty. The objective of this study is to ascertain the direct impact of gamification on customer loyalty and its indirect influence on brand engagement and customer experience. This research uses an explanatory research approach with a population of Shopee customers who have engage with Shopee Games. The sampling technique used was non-probablity samping, with a total of 119 respondents. Data was collected through an online survey using Google Forms and analyzed using the Structural Equation Modeling Partila Least Square (SEM-PLS) method using SmartPLS 3.0 software. The finding of this study show that gamificaiton does not have a signigicant effect on customer loyalty, while gamification have significant effect on brand engagement and customer expericence. Brand engagement and customer experience have significant influence on loyalty. In addition, customer experience and brand engagement are variabel that have mediating effect between gamification and customer loyalty. These finding provide important insight for tech-company manager in designing strategies to increase customer loyalty on their bussinesses
Reaploud Repository February_Hasyim
Keywords: Gamification; Customer Experience; Brand Engagement and Customer Loyalty